2009
DOI: 10.1073/pnas.0903863106
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana craving in the brain

Abstract: Craving is one of the primary behavioral components of drug addiction, and cue-elicited craving is an especially powerful form of this construct. While cue-elicited craving and its underlying neurobiological mechanisms have been extensively studied with respect to alcohol and other drugs of abuse, the same cannot be said for marijuana. Cue-elicited craving for other drugs of abuse is associated with increased activity in a number of brain areas, particularly the reward pathway. This study used functional magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
191
2
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 237 publications
(212 citation statements)
references
References 75 publications
14
191
2
4
Order By: Relevance
“…Traditionally, craving has been associated with brain areas related to reward, motivation and memory, including prefrontal cortical areas (Grant et al, 1996); the striatum and ventral pallidum (Filbey et al, 2009;Wetherill et al, 2013); mesolimbic dopamine structures such as the ventral tegmental area (Goudriaan et al, 2013); and reward memory areas like the amygdala or the hippocampus (Kilts et al, 2001;Volkow et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Traditionally, craving has been associated with brain areas related to reward, motivation and memory, including prefrontal cortical areas (Grant et al, 1996); the striatum and ventral pallidum (Filbey et al, 2009;Wetherill et al, 2013); mesolimbic dopamine structures such as the ventral tegmental area (Goudriaan et al, 2013); and reward memory areas like the amygdala or the hippocampus (Kilts et al, 2001;Volkow et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous human neuroimaging studies have demonstrated activation in the cerebellum during the presentation of drug-associated cues (Anderson et al, 2006;Filbey et al, 2009;Grant et al, 1996). In almost every study, craving was elicited by the presentation of the cue.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations